Performing puja of the Grihadevata - Mumbai Archive Project Team (Jio Institute, 2024)
The women of the house perform puja ceremonies dedicated to the grihadevata (tutelary deity) Garli Devi and Karjai Devi. Garli Devi, or Garli Mata, is considered a protector of fishermen and their families, ensuring their safety and prosperity. Karjai Devi, or Karjai Mata, is venerated as the guardian of fishermen, safeguarding them at sea and providing protection from natural calamities and dangers.